Validation of Affect-tag Affective and Cognitive Indicators - Sparrow, Laurent; Six, Hugo; Varona, Lauren; Janin, Olivier (Frontiers in Neuroinformatics, 2021)
The Affect-tag solution measures physiological signals to deliver indicators derived from cognitive science. In order to provide the most accurate and effective results, a database of electrodermal activity signals acquired using the Affect-tag A1 band was created. An experimental paradigm was designed to measure action-taking, autonomic regulation, cognitive load, emotions and stress, affects, and social stress. The Affect-tag Emotional Power, Emotional Density, and Cognitive Load affective and cognitive indicators were refined based on the physiological responses of 48 participants during these tasks. Statistical significance was obtained for all indicators in tasks they were designed to measure resulting in a total accuracy score of 89% for the combined indicators. Data obtained during this study will be further analyzed to define emotional and affective states